The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1108/08858620510603927
|View full text |Cite
|
Sign up to set email alerts
|

Creating digital value: at the heart of the I‐E‐I framework

Abstract: Purpose -The purpose of this study is to provide a better understanding on the use of web sites for creating value in industrial buyer-seller relationships. Design/methodology/approach -Through an extensive yet not exhaustive review of previous studies on business-to-business (B2B) web site development, the extranet level of a conceptual model (the I-E-I framework) is tested in an industrial setting in Sweden. Using four research questions as a guide, a qualitative, case study approach is followed in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Several previous studies have identified issues meriting further research, such as how firms use digital communications channels and how use of these channels affects buyer-seller relationships (Constantinides & Fountain, 2008;Day & Bens 2005;Foster, 2005;Hennig-Thurau et al, 2010;Järvinen et al, 2012;Kerrigan & Graham, 2010;Michaelidou et al, 2011;Mulhern, 2009;Parasuraman & Zinkhan, 2002) This study proceeds as follows: We first provide a review of extant literature to determine the characteristics of industrial marketing communications and DMC. We then deepen theoretical understanding with an empirical multiple case study.…”
Section: Article Classification Research Papermentioning
confidence: 99%
See 3 more Smart Citations
“…Several previous studies have identified issues meriting further research, such as how firms use digital communications channels and how use of these channels affects buyer-seller relationships (Constantinides & Fountain, 2008;Day & Bens 2005;Foster, 2005;Hennig-Thurau et al, 2010;Järvinen et al, 2012;Kerrigan & Graham, 2010;Michaelidou et al, 2011;Mulhern, 2009;Parasuraman & Zinkhan, 2002) This study proceeds as follows: We first provide a review of extant literature to determine the characteristics of industrial marketing communications and DMC. We then deepen theoretical understanding with an empirical multiple case study.…”
Section: Article Classification Research Papermentioning
confidence: 99%
“…Companies now acknowledge the need to listen to their customers more, engage them in conversation, be transparent, and communicate with them openly and 3 empathetically. The marketing specialist's role has evolved from being a broadcaster to being an aggregator who brings content together to enable collaboration and participation in communities.Marketing communications now includes creating online communities, generating leads from online environments, and collaborating with customers to gain a better understanding of their needs (Weber, 2009).Several previous studies have identified issues meriting further research, such as how firms use digital communications channels and how use of these channels affects buyer-seller relationships (Constantinides & Fountain, 2008;Day & Bens 2005;Foster, 2005;Hennig-Thurau et al, 2010;Järvinen et al, 2012;Kerrigan & Graham, 2010;Michaelidou et al, 2011;Mulhern, 2009;Parasuraman & Zinkhan, 2002) This study proceeds as follows: We first provide a review of extant literature to determine the characteristics of industrial marketing communications and DMC. We then deepen theoretical understanding with an empirical multiple case study.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is essential to know the service characteristics that drive customer value, and companies must know why people engage their services to develop appropriate service strategies 31 . Mackenzie 32 believes that product performance and product quality are the basic conditions for a core product.…”
Section: H3 the Satisfaction That The Retailer Feels In The Electronmentioning
confidence: 99%